Rapid, Universal Method to Isolate PCR-Ready DNA Using Magnetic Beads. (March 1997) - Rudi, K.; Kroken, M.; Dahlberg, O.J.; Deggerdal, A.; Jakobsen, K.S.; Larsen, F.
A magnetic bead-based system for DNA isolation utilizing monodisperse beads was tested with the aim of producing a general approach for PCR-ready DNA. This commercially available system was originally designed for isolating PCR-ready DNA from human whole blood. We tested diverse organisms belonging to the major groups: bacteria, fungi, algae, vascular plants and vertebrates. Optimization of sample amounts and lysis conditions was done using several types of tissue (fish epithelium, plant leaves, mammalian liver and muscle tissues, fungal fruit-bodies and mycelium). The standard lysis conditions used for blood could be applied with good results for most bacteria, algae and vertebrates, while plant leaves and fungal fruit-bodies had to be mechanically broken to obtain proper lysis. For vascular plants and some cyanobacteria, lysis by heating to 65°C gave better DNA yields than standard lysis at room temperature. In all cases, DNA suitable for PCR was prepared in less than 30 min. The PCR products yielded 350 to 500 bases of DNA sequence (99% accurate) by direct manual or automated sequencing.